Security in The Arctic: The Decline of Arctic Exceptionalism? Between Cooperation and Militarization - Hagen, Victoria Berg (AUC Knowledge Fountain, 2026)
The Arctic has been understood as a region separated from international relations, where states choose to collaborate and maintain stability (Gjørv et al. 2020: 2). This has led to the creation of the concept of “Arctic Exceptionalism” (Heininen 2019: 226). Currently, the Arctic is becoming strategically important. Furthermore, the region is witnessing militarization and increased international tensions affecting the Arctic states (Padrtova 2020: 38). This thesis analyzes how Arctic exceptionalism, as reflected in bilateral relations (specifically Russia-Finland and Russia-Norway), has been impacted by the Donbas War, the invasion of Ukraine, and militarization in the Arctic by both NATO and Russia. This thesis addresses these case studies by examining the historical and current relations between the states through the lenses of Walt’s (1987) balance of threat and constructivism. This thesis finds that security dynamics outside of the region have impacted Russia’s relations with Finland and Norway, but this thesis argues that this threat perception is rooted in their historical relations about the “other”. Through analyzing their relations using historical pattern analysis and the lens of balance of threat, this thesis concludes that Arctic exceptionalism was never about a region that is separated from international relations. Rather, it was a strategy to navigate their security concerns about the “other” in line with the theory of realism and using “liberalism” as an instrument. Constructivism provides a lens in understanding that “Arctic exceptionalism” failed to build the norm in erasing historical security perceptions leading to the demise of the notion (strategy) under changing circumstances.